Employment, work ability and sick leave in melanoma patients within the first year of diagnosis - Dugas-Breit, Susanne; Dugas, Martin; Schulze, Hans-Joachim (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
Background and objectives Malignant melanoma affects younger working individuals. This study investigated work ability and sick leave within one year after diagnosis, as well as the impact of rehabilitation and psycho-oncological measures on employment outcomes. Patients and methods In this monocentric, prospective, observational cohort study, 221 patients (62.4% females), aged 19-65, participated. 78.5% had tumor stage IB or lower at baseline. Routine clinical documentation, occupational history, work ability, subjective prognosis of employment, need for and satisfaction with rehabilitation measures were repeatedly assessed. Results 181 patients (82%) were employed at first visit, 172 (78%) at last visit. Approximately 75% of patients initially rated work ability as “moderate”, with up to 9 sick leave days. In the following year, sick days increased significantly in patients with stage IB and IIA (p = 0.044) and highly significantly in patients with stage II B and above (p < 0.001). Psycho-oncologic consultation (24%) and rehabilitation (18%) did not change the significantly worse self-rated work ability of these patients. Conclusions Melanoma affects work ability, even in tumor stages without lymph node involvement or distant metastasis. Controlled clinical trials would be useful to evaluate the success of rehabilitation and psycho-oncological interventions for patients with melanoma.
Online veröffentlicht: 26 October 2024
Gesehen am 24.03.2025